OPTICAL AND MöSSBAUER SPECTROSCOPY OF IRON IN MICAS - Dyar M.D. (My University, 2002)
The spectroscopic study of iron in micas is generally focused on one or both of two goals: determination of the relative amounts of Fe2+ and Fe3+ present, and assessment of the distribution of those ions among the one tetrahedral and two octahedral sites in the mica structure. Historically, nine different means have been used to address these goals: wet chemistry, optical, Mossbauer (MS), synchrotron X-ray absorption near-edge (XANES), X-ray photoelectron (XPS), and electron energy-loss spectroscopies (EELS), electron microprobe (EPMA), indirect calculation methods, and X-ray diffraction structure refinements (SREF). Sample requirements for all these techniques vary from the need for oriented, doubly-polished single grains to large quantities of homogeneous powder. Bulk sample analysis (milligram and larger masses) requires significant analyst skills, is done reliably at relatively few laboratories and has been controversial (particularly with the Mossbauer community). Measurements at the scale of microbeam analysis (picogram) have historically yielded inconsistent results (in the case of electron microprobe or indirect calculation methods) or have been until very recently confined to a few experimental studies. Because of these problems and the dichotomy of scale between the available analytical techniques, the importance of oxidation state measurements has often been ignored during the last 40 years despite (and in some cases, because of) the efforts of the spectroscopic community. However, the ability to measure the oxidation states and site occupancies of Fe in micas, particularly at micrometer scales, has long been a necessity for mineralogists, petrologists, and geochemists. In this paper, existing work on the primary spectroscopic methods for studying Fe in micas is discussed and reviewed. Other techniques will not be covered in detail here for a variety of reasons: Site assignments for Fe and other cations can be made using structure refinements based upon X-ray diffraction studies, and that subject is well …